BREAST FEEDING PATTERNS IN SOME LACTATING MOTHERS OF RAWALPINDI: Breastfeeding Patterns - Sabir, Syed Arshad; Ramzan, Mussarat (Pakistan Armed Forces Medical Journal, 2008)
Objectives: The purpose of the study was to assess present patterns of breast feeding (BF) to identify such determinants that can be positively modified in the present socioeconomic scene of the nation. Design: It was a descriptive cross sectional study. Place and Duration of Study: This study was done in Rawalpindi city from March 2004 to December 2004. Subjects and Methods: Mother’s perceptions (n=501) for breast feeding (BF) were examined through a descriptive cross-sectional study using convenient sampling technique in urban area of Rawalpindi city. National (BF) policy guidelines were used as a basis of assessment. Results: Lactational practices were not optimum in majority (87.42%) and in all socioeconomic strata. In general no significant association was found between Literacy and economic strata and the pattern of (BF) of the study population (P> 0.1 & > 0.05 respectively). However, practice of additional food intake during Lactational period was significantly associated with right breast feeding practices in the population studied (P < 0.05 & odd’s ratio 7.2).  In 29.2% cases qualified health care providers including specialist in obstetrical care promoted formula milk feeding. Conclusion: Insufficient information, Ineffective motivation about BF of masses and inappropriate healthcare practices, were major factors responsible for inadequate (BF) practices in the community studied. The issue can be addressed by enhancing health education to potential mothers, sensitizing males and effective monitoring of health care practices.